Problematika Pendidikan Anak Di Keluarga Muslim Buruh Pabrik: (Studi Kasus Keluarga Pekerja Pabrik Rokok Diva Sejahtera Sidoarjo) - M. Badrul Huda el Haque (Program Studi Pendidikan Islam Anak Usia Dini, 2021)
Abstract:. Religious education in children is first obtained from the family environment and the main component is parents. The presence of parents in raising children is one thing that cannot be underestimated and ordinary. The absence of parents in the family will result in children being